A Systematic Review of SNPs Screening for Platinum-Related Pharmacodynamics and Pharmacokinetics Genes in Non-Small Cell Lung Cancer for Precision Medicine - Afifah NN; Larasati AL; Wijaya I; Zakiyah N; Intania R; Obinata H; Barliana MI (The Application of Clinical Genetics)
Nadiya Nurul Afifah,1,2 Annisa Lazuardi Larasati,3 Indra Wijaya,4 Neily Zakiyah,5,6 Ruri Intania,7 Hideru Obinata,8 Melisa Intan Barliana1,6 1Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Department of Pharmacy, Faculty of Health Sciences, Universitas Esa Unggul, Jakarta, Indonesia; 3Faculty of Pharmacy, Universitas Indonesia, Depok, Indonesia; 4Department of Internal Medicine, Hasan Sadikin General Hospital, Bandung, Indonesia; 5Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 6Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, Indonesia; 7Rotinsulu Lung Hospital, Bandung, Indonesia; 8Department of Biochemistry, Gunma University School of Medicine, Maebashi, JapanCorrespondence: Melisa Intan Barliana, Email melisa.barliana@unpad.ac.idIntroduction: Traditional treatments for non-small cell lung cancer (NSCLC), such as chemotherapy, especially platinum-based regimens, often lack efficacy due to the disease’s inherent heterogeneity. Precision medicine in NSCLC recognizes each tumor’s unique genetic profile. Alterations in the pharmacokinetics and pharmacodynamics of platinum-based therapies significantly influence their clinical outcomes. Previous research has predominantly focused on genetic polymorphisms in genes like Glutathione S-transferase Pi 1 (GSTP1), ATP Binding Cassette subfamily C member 2 (ABCC2), Excision repair cross-complementation group 1 and 2 (ERCC1, and/ ERCC2), which play crucial roles in detoxification, drug transportation, and Nucleotide Excision Repair (NER). However, findings have shown considerable variability.Methods: The analysis followed the PRISMA and STROPS Guidelines, using specific search terms including NSCLC, Chemotherapy, Polymorphisms, Single Nucleotide Polymorphisms (SNPs), ERCC1, ERCC2, ABCC2, GSTP1, Effectiveness, and Clinical Response. These studies were subjected to full-text screening process.Results: Initial screening of 370 studies, comprising 275 from PubMed and 95 from EBSCO, identified 53 relevant ones, excluding those such as reviews, non-English studies, and meta-analyses. Among the genetic variants studied (ERCC1 rs11615, ERCC2 rs13181, ABCC2 rs717620, GSTP1 rs1695), GSTP1 rs1695 emerged as particularly promising, with 11 studies indicating a significant association with improved survival outcomes.Conclusion: The integration of SNP profiling into clinical decision-making processes holds substantial potential for enhancing the personalization of NSCLC treatment strategies, thereby improving patient outcomes.Keywords: NSCLC, chemotherapy, polymorphisms, SNPs, ERCC1, ERCC2, ABCC2, GSTP1